PELATIHAN PEMBUATAN PRODUK SUSU PROBIOTIK-SARI BUAH BAGI KELOMPOK WANITA TANI DUSUN WONOREJO KOTA BATU - Nuzul Wahyuning Diyah (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2020)
The cow milk collected in KUD Batu has reached 16-17 tons per day. The most product is fresh dairy milk and only small amount of processed products. The target community had no experiences in processing cow milk using probiotic microbes yet. The objectives was transfering of science and technology about the production of probiotic milk combined with fruit juice. This program was specifically directed to increase the empowerment of Kelompok Wanita Tani "Wonoasri" in Wonorejo-Batu, in developing probiotic dairy products combined with fruit juice to increase the diversification of products with higher economic value. The method included workshop and technical assistance, which were carried out in a serie of steps: 1) exploring the knowledge of target by surveys and pre test, 2) lecturing and discussion, 3) demonstrating how to prepare and characterize the probiotic milk products, 4) training of product preparation, 5) product characterization and packaging assistance, 6) evaluation. The results were the target community gained increase in knowledge and experience, and they could produce fruity probiotic milk. In addition, they would increase their understanding and enthusiasm to appreciate the potency of their territory in order to improve the nation's competitiveness. Key words : probiotic milk-fruit juice, workshop, kelompok wanita tani, wonorejo